Translation in context: a descriptive account of Romeo and Juliet in versions by Konstantin Bal’mont and Anna Radlova - Wood, KF (2020)
This thesis will analyse two translations of Romeo and Juliet completed in the early years of the Soviet Union: one produced by Konstantin Bal’mont in 1919, the other by Anna Radlova in 1934. The research will use the Descriptive Translation Studies framework, particularly Gideon Toury’s idea of translation norms, in order to try to account for some of the choices made in both translations, as well as for the reception of these translations.